2017
DOI: 10.1080/0020739x.2017.1305130
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing student engagement to positively impact mathematics anxiety, confidence and achievement for interdisciplinary science subjects

Abstract: Contemporary science educators must equip their students with the knowledge and practical know-how to connect multiple disciplines like mathematics, computing and the natural sciences to gain a richer and deeper understanding of a scientific problem. However, many biology and earth science students are prejudiced against mathematics due to negative emotions like high mathematical anxiety and low mathematical confidence. Here, we present a theoretical framework that investigates linkages between student engagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 22 publications
0
35
0
7
Order By: Relevance
“…Student engagement is an important aspect of motivation (Linnenbrink, & Pintrich, 2003). Everingham et al (2017Everingham et al ( , p. 1154 stated, "… evidence for the effectiveness of student engagement for learning and subject mastery is overwhelming". Everingham et al (2017) pointed that few studies that have investigated the effect of engagement on mathematics anxiety.…”
Section: Engagement In Mathematicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Student engagement is an important aspect of motivation (Linnenbrink, & Pintrich, 2003). Everingham et al (2017Everingham et al ( , p. 1154 stated, "… evidence for the effectiveness of student engagement for learning and subject mastery is overwhelming". Everingham et al (2017) pointed that few studies that have investigated the effect of engagement on mathematics anxiety.…”
Section: Engagement In Mathematicsmentioning
confidence: 99%
“…Everingham et al (2017Everingham et al ( , p. 1154 stated, "… evidence for the effectiveness of student engagement for learning and subject mastery is overwhelming". Everingham et al (2017) pointed that few studies that have investigated the effect of engagement on mathematics anxiety. Everingham et al (2017) used some strategies to engage students in mathematics and science and found those strategies overcome mathematical anxieties.…”
Section: Engagement In Mathematicsmentioning
confidence: 99%
See 3 more Smart Citations